Construção de uma vacina de subunidade proteica de mycobacterium tuberculosis e avaliação da imunogenicidade e antigenicidade - Sousa, Eduardo Martins de (2013)
Tuberculosis is a re-emerging infectious disease that remains a major public health problem worldwide. Although there is the BCG vaccine that is effective against severe forms of childhood TB, in adults its efficacy is variable (0-85%). In this context there is a need to develop new vaccines to control the spread of TB. This thesis proposes the development of a new recombinant fusion M. tuberculosis protein (Ag85C-MPT51-HspX) by molecular cloning, expression in E. coli with a histidine tag and purified by ion exchange chromatography. The fusion protein was constructed successfully, expressed in E. coli BL21 and purified. Tests in mice were performed to evaluate the immunogenicity of the recombinant fusion protein Ag85C-MPT51-HspX of M. tuberculosis. Mice were immunized three times with the protein Ag85C-MPT51-HspX formulated with CpG-DNA encapsulated in liposomes, CpG-DNA encapsulated in liposomes, liposome or saline as negative control and the humoral and cellular immune response was evaluated. The immunization with the vaccine formulation induced the production of high titers of specific anti-fusion protein Ag85C-MPT51-HspX IgG1 = 3.08 ± 0.04; IgG2a = 3.10 ± 0.03) and, favored the increase of specific CD4+ IFN-γ (2.14% ± 0.17), CD4+ TNF-α (2.16 ± 0.34%). The recognizing of this protein by seric IgG and IgM discriminated patients with active TB infection from healthy individuals. We conclude that CMX protein has potential to be used for the development of vaccine against M. tuberculosis as well also for TB diagnostic kits.